Pengembangan E-Modul Praktikum Laundry Berbasis Standar Operasional Prosedur (SOP) Di SMK Negeri 1 Singaraja - Putu Kharisma Febriyanti; Risa Panti Ariani; Made Riki Ponga Kusyanda (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This study was motivated by the lack of digital learning media that specifically provides pratical guidance for laundry activities based on Standard Operating Prosedures (SOP) at SMK Negeri 1 Singaraja. The learning process still relies on conventional method, causing students to have difficulty understanding SOP properly. This study aims to develop an SOP based laundry practicum e-module focusing on linen washing competence using 4D decelopment model. This research is Research and Development (R&D) study consisting of four stages, define, design, develop, and disseminate. The validity of the e-module was assessed by two material experts and two media and design experts. The resultes showed that the developed e-modul was valid and suitable for use as a learning medium. The material expert validation obtained a ascore of 100%, while the media and design validation reached 98.75%, both categprized as very good. The e-module presentes systematic learning content based on SOP, supported by images, videos, and quizzez to facilitate independent learning. Therefore, this e-module can effectively support student in understanding and implementing laundry procedures in vocational education.